Mentoring urban Black Middle-School Male Students: Implications for Academic Achievement - Gordon, Derrick M. (2009)
Researchers have called for innovative and culturally responsive intervention programs to enhance male, African American middle school students’ academic achievement. Mentoring has received considerable attention as a novel remedy. Although anecdotal evidence supports the positive role of mentoring on academic achievement, these results are not consistent. The Benjamin E. Mays Institute (BEMI) builds on the ideals of mentoring to counter the effects academic underachievement among adolescent Black males by building a model that is Afro-centric, uses pro-social modeling, and emphasizes cultural strengths and pride, and single-sex instruction in a dual-sex educational environment. Sixty-one middle-school Black males were enrolled (BEMI: n=29; Comparison: n=32) in this study. Results revealed that students in the BEMI program had significantly greater academic attachment scores and academic success than their non-mentored peers. Additionally, racial identity attitudes of immersion/emersion and internalization and identification with academics were also significantly associated with standardized achievement tests and GPA. Policy and practice implications are discussed.